Knowledge, attitudes and perceptions towards utilization of bilateral tubal ligation among married women of reproductive age (15-49 years) in Kasgunga Ward, Homabay County, Kenya - Kibet, Phylis J.; Okeyo, Jane A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Approximately 20% of women of reproductive age in developing countries would prefer to ultimately stop bearing children after attaining their desired family size, however, they are faced with over 26% rate of unmet modern family planning methods such as bilateral tubal ligation (BTL). Objectives were to assess knowledge, attitude and perceptions on the utilization of BTL among the married women in Kasgunga ward and to measure the association between education level, income, number of children and the use of BTL. Methods: A cross-sectional study design was used to collect data related to knowledge, attitude and perceptions among 399 married women in Kasgunga Ward, Homabay County, Kenya. Results: Only 36 (35.1% of those who had reached the desired number of children said they would consider using BTL after discussing it with their husbands. Eighty-two (79.6%) of study participants cited not considering busing BTL as it was against their culture, and 137 (66%) that it was against their religious beliefs. Forty-nine (47.2%) of the women would go on to have BTL, whether or not their husbands approved of it. The cross-tabulation indicated that the use of BTL was most common among women with more than 5 children (80.0%) compared to 20.0% in women with 3-5 children and none in those with 0-2 children, with a statistically significant association, χ²(2)=107.75, p<0.001. Conclusions: This study demonstrated that knowledge, attitudes, and perceptions influence the utilization of BTL among married women of reproductive age.